Transformasi Sosial di Pedesaan: Dampak Industrialisasi Terhadap Kehidupan Masyarakat Lokal - Syamsul Wathoni (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
The aim of writing this work is to determine social transformation in rural areas: the impact of industrialization on the lives of local communities. The research begins by exploring social transformation in rural areas through a literature review, using theoretical works from leading sociologists. Data sources include academic documents, village archives, and community participation through interviews and surveys with questionnaires. The collected data was analyzed using a qualitative approach for nuances and dynamics, and a quantitative approach for a numerical description of the impact of industrialization. This research produces a holistic narrative that combines theoretical foundations, empirical data, and qualitative and quantitative analysis, exploring social transformation in rural areas due to industrialization. The result of this work is that the wave of industrialization has significantly changed the economic structure and lifestyle of rural communities, bringing new hopes and challenges. Although economic progress and educational improvements were achieved, negative impacts such as social disapproval and inequality emerged. Infrastructure plays a key role in opening positive opportunities and strengthening regional integration. The sociological perspectives of prominent figures provide deep insight into social and cultural change in rural areas. Wise management is the key to maintaining a balance between economic growth and social welfare in the course of adaptation through waves of industrialization.